Facile approach to synthesize, compared to MgO & ZnO nanoparticles by using Clitoria ternatea/Tecoma castanifolia flower. (2020) - Priya, P.; Elumali, K.; Shakila, D.; Geetha, K.; Dinesh Karthik, A.
Highlights: To Synthesis of MgO Nanoparticles Using delonix elata plant Extract from Mg(OH)2 P1 Precursor by eco friendly method. To Synthesis of ZnO Nanoparticles Using Tecoma castanifolia ﬂower Extract from Zinc Sulphate P1 Precursor by eco friendly method. High yield by a novel Eco friendly technique at a high temperature. Abstract: In this Study the metal oxide nanoparticles are getting an extended thought in various biomedical applications, for instance, to treat cancer prevention agent properties, antimicrobial action, gas sensors, alluring sun based imperativeness change, lithium molecule cathode materials, semiconductors and catalysis. The Nanoparticles were set up by the eco cordial strategy with various plants materials utilized as a surface modifier and stabilizer. Magnesium oxide nanoparticles (MgO) and Zinc Oxide nanoparticles (ZnO) were fused by using leaf as the in a green amalgamation technique. So in this paper the fundamental eco friendly synthesis method, antibacterial activity antioxidant activity and antibacterial mechanisms of MgO & ZnO nanoparticles are review.